Student Activism Remains a Potent Force Worldwide - Altbach, Philip G; Klemencic, Manja (International Higher Education, 2014)
Student activism remains a potent force worldwide. Recently, students were instrumental in the collapse of the regime in Ukraine, and were key forces in the Arab Spring movements. Students, however, are unable to ensure that their views will be reflected in the governments that emerge from unrest. Students also are active participants in campus events, and have often been instrumental in shaping higher education policy.